Benefits of Green Seaweed as Protein Source for Broiler: A Review - Listya Purnamasari; Janine M. Carreon; Joseph F. dela Cruz (Universitas Tidar, 2022)
Poultry production contributes significantly to the agricultural economy. Nutrition is one important factor in having competent poultry production. Currently, there is a lot of research about natural alternatives or feed additives that are low in cost and can help increase the overall performance and improve poultry health conditions without any adverse effects. Macroalgae such as green seaweeds can meet these parameters. It is easily available and is considered a rich source of proteins, polysaccharides, carbohydrates, vitamins, minerals, pigments, and antioxidants. Most often, seaweeds are used as feed additives for broiler chickens as they can induce a beneficial impact on production parameters (body weight (BW), average daily gain (ADG), feed consumption (FC), and feed conversion ratio (FCR) and meat quality. However, there are several challenges in using green seaweed as a protein alternative for broiler chickens such as its toxic and antinutritional components, as well as varying available supply due to seasonal effects, diseases, location, and environmental pollution. Furthermore, the main objective of this review is to evaluate the different research conducted on green seaweed as a potential protein source in broilers.